Two aphid species newly introduced in Greece - Margaritopoulos, J. T.; Papapanagiotou, A. P.; Voudouris, C. Ch.; Kati, A.; Blackman, R. L. (ENTOMOLOGIA HELLENICA, 2013)
In this paper we report two aphid species as new records for the Greek and the European aphid fauna. The species are Aphis odinae (van der Goot) and Melanaphis sorghi (Theobald) (Hemiptera: Aphididae). The former was found on Pittosporum spp. in Thessaloniki, northern Greece, and the latter on Sorghum halepense (L.) in Messolonghi, southern Greece, and also in Thessaloniki. Heavy infestations in Pittosporum trees by A. odinae have not been observed and M. sorghi was not detected in cultivated sorghum or maize in the few inspections we made. Thus, according to our inspections neither of these species is as yet of economic importance in Greece. These two species increase the number of aphid species recorded in Greece to 335.